Profitability in milk production in operation flood areas of Assam - BARUAH, D K; SARKER, A B (The Indian Journal of Animal Sciences, 2013)
The data on 850 stall-fed Jersey grades (Jersey x local) maintained as marginal, lower, medium, upper medium and large unit size in ’operation flood’ areas of Assam, were analysed to study the profitability in milk production by taking into consideration various costs and return traits. The analysis revealed that overall mean of total return, total feed cost, ROFC, return from milk, milk yield, total fixed cost, total variable cost, ROVC, and total cost including and excluding unpaid (family) labour/animal a year were Rs 19 262.49, Rs 12 062.99, Rs 7 199.59, Rs 18 018.03,2023.58 litres, Rs 2 159.03, Rs 14 929.59, Rs 4332.90 and Rs 17 088.62 and Rs 15 611.43 respectively. While the feed cost efficiency, FC : VC, variable cost/litre, price/litre of milk,’break-even output, per cent of break-even output to total output, and input-output ratio including and excluding unpaid labour were recorded as 59.68% 1 : 6.91, Rs 7.38, Rs 8.90, 1420.41 litres, 70.19 and 1.13 and 1.23 respectively. The lower unit size was more profitable in study areas in comparison to other unit sizes. Therefore it may be concluded that dairying with atleast ’4’ numbers of high yielding Jersey graded cows is an economically viable and profitable proposition in Assam.